Medical complications, clinical findings, and educational outcomes in adults with Noonan syndrome - Smpokou, Patroula; Tworog-Dube, Erica; Kucherlapati, Raju S.; Roberts, Amy E. (American journal of medical genetics. Part A, 2012)
Noonan syndrome (NS) is a heterogeneous developmental disorder caused by missense mutations in genes involved in the Ras/MAPK signaling pathway, a major mediator of early and late developmental processes. The diagnosis of NS is made on clinical grounds with molecular confirmation of a mutation found in 63% of cases. Key clinical features include short stature, cardiac defects, developmental delay, lymphatic dysplasias, bleeding tendency, and a constellation of distinctive facial features and physical exam findings. The prevalence of medical issues or the development of new ones in adults with NS is not well‐studied. This cross‐sectional study reports on the prevalence of clinical conditions and their ages of onset in a cohort of 35 adolescents and adults with NS aged 16–68 years old (mean age 28 years). In this cohort, 34 of 35 subjects (97%) had had full PTPN11 sequencing; 37% were PTPN11 positive, 23% were SOS1 positive, and 3% were BRAF positive. Mean adult height in both men and women was at the 3rd–10th centile. The most prevalent clinical findings in this cohort included pulmonary valve stenosis (71%), easy bruising (63%), GERD (60%), constipation (51%), scoliosis (54%), chronic joint pain (54%), lymphedema (49%), depression (49%), anxiety (49%), Chiari malformation (20%), and osteopenia/osteoporosis (14%). In summary, adults with NS are affected by multi‐organ morbidity and require special medical management aimed towards the most prevalent and serious known medical complications. Larger studies characterizing the clinical conditions found in NS adults are needed to provide potential genotype–phenotype correlations that may aid in clinical management. © 2012 Wiley Periodicals, Inc.